2010
DOI: 10.1177/8755123310378452
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Differences Between Early and Late Degree Program Music Teacher Education Students Using a Concise Emotional Inventory

Abstract: Teaching music can be a stressful profession. How current and future teachers perceive stress, and the personal emotions that result from stressful situations, raises many questions. This study investigated differences in perception of levels of emotional stress between early and late program students in music teacher education using a concise emotional inventory. The scale was developed as an expedient device to be used with young adults to access a person's emotional state across a wide variety of defined li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Few researchers have made direct comparisons between novice and experienced music teachers, especially with regards to resilience factors. Fredrickson and Madsen (2010) analyzed stressors related to music education, but their research was focused on preservice music teachers. Conway et al (2018) compared the workplace experience of experienced and novice teachers within the realm of micropolitics and found that the level of comfort with workplace interactions was connected to level of experience.…”
mentioning
confidence: 99%
“…Few researchers have made direct comparisons between novice and experienced music teachers, especially with regards to resilience factors. Fredrickson and Madsen (2010) analyzed stressors related to music education, but their research was focused on preservice music teachers. Conway et al (2018) compared the workplace experience of experienced and novice teachers within the realm of micropolitics and found that the level of comfort with workplace interactions was connected to level of experience.…”
mentioning
confidence: 99%